Use of regulatory cells for achieving functional tolerance of pig heart xenotransplants in humans: a literature review - Braileanu, Gheorghe Traian (Frontiers in Immunology, 2025)
Xenotransplantation of pig hearts may help address the current human shortage of human donors once rejection is controlled. One innovative approach to combat rejection in humans is the use of regulatory cell (RC) therapy. The term RC refers to all cell populations that share immunosuppressive functions. The use of RC, including mesenchymal stem cells (MSC) and CD4+CD125lowCD25highFoxp3+ T cells (Treg), may potentially reduce or eliminate the need for chronic general immunosuppression (IS). This approach is hypothesized to act by augmenting suppressive immune mechanisms that maintain tolerance by prevailing over the immune effector mechanisms responsible for rejection. Increasing RC numbers through adoptive cell transfer (ACT) and enhancing their functions via chimeric antigen receptor (CAR) technology are two promising strategies for RC therapy applications. During the various steps of rejection, monitoring specific biomarkers can guide the use of the corresponding RC subpopulation, preferably available off-the-shelf, either alone or in combination, administered once or multiple times. In the future, exosomes or RC-derived active molecules (or their antagonists) may supplement or replace whole-cell therapy. With further research, RC therapy, which has not yet been used in clinics to induce functional tolerance to pig heart xenotransplants in humans, has the potential to become a routine, personalized treatment.